Microbiome Development of Seawater-Incubated Pre-production Plastic Pellets Reveals Distinct and Predictive Community Compositions - Ward, Christopher S.; Diana, Zoie; Ke, Kate Meicong; Orihuela, Beatriz; Schultz, Thomas P.; Rittschof, Daniel (Frontiers in Marine Science, 2022)
Plastics of various chemistries pollute global water bodies. Toxic chemicals leach with detrimental and often unpredictable impacts on the surrounding ecosystems. We found that seawater leachates of plastic pre-production pellets from 7 recycle categories are acutely toxic to stage II barnacle nauplii; lethal concentration 50 (LC50s) were observed in 24-h leachates from dilutions ranging from 0.007 to 2.1 mg/mL of seawater. Based on previous observations that macro-organismal settlement on fouling management coatings of various toxicities can be used to predict the toxicity of the coating, we hypothesized that interaction of plastic pre-production pellets with emerging microbiomes would exhibit patterns indicative of the chemistry at the pellet surface. We used amplicon sequencing of bacterial 16S ribosomal RNA genes to characterize the microbiomes that developed from 8 through 70 days on pellets exposed to the same flowing ambient seawater. Diversity and composition of the microbiomes colonizing plastic pellets changed over time and varied with plastic type. Microbial taxa belong to taxonomic groups known to consume hydrocarbons, to be prevalent following marine oil spills, or to live on fouling management surfaces. Microbiomes were still distinct between plastic types at Day 70, suggesting that differences in the physicochemical characteristics of the underlying plastics continue to exert variable selection of surface microbial communities. A random forest-based sample classifier correctly predicted 93% of plastic types using microbiome compositions. Surface microbiomes have promise for use in forensically identifying plastic types and potential toxicities.